2013
DOI: 10.6018/analesps.29.2.136401
|View full text |Cite
|
Sign up to set email alerts
|

Aburrimiento y disfrute en clase de Lengua española en secundaria: predictores motivacionales y efectos sobre el rendimiento

Abstract: Resumen: Este trabajo intenta analizar, mediante un modelo de ecuaciones estructurales, las relaciones entre motivación autodeterminada, aburrimiento, disfrute y rendimiento en clase de Lengua. La muestra estuvo compuesta por 642 estudiantes de secundaria españoles, con edades comprendidas entre 12 y 18 años, que fueron evaluados en tres momentos sucesivos. Los resultados mostraron que la motivación intrínseca y la regulación identificada predijeron positivamente el disfrute y el rendimiento, y negativamente e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
1
12
0
7
Order By: Relevance
“…The task value is one of the value appraisals most frequently studied in relation to boredom (Goetz, Frenzel, Stoeger, & Hall, 2010;Goetz et al, 2006;González et al, 2013;Nett et al, 2010;Pekrun et al, 2010;Sánchez Rosas & Bedis, 2015;Tze, 2011). When an activity is negatively valued negative emotions like boredom will instigate (Pekrun & Perry, 2014).…”
Section: Self-efficacy Task Value and Boredommentioning
confidence: 99%
See 2 more Smart Citations
“…The task value is one of the value appraisals most frequently studied in relation to boredom (Goetz, Frenzel, Stoeger, & Hall, 2010;Goetz et al, 2006;González et al, 2013;Nett et al, 2010;Pekrun et al, 2010;Sánchez Rosas & Bedis, 2015;Tze, 2011). When an activity is negatively valued negative emotions like boredom will instigate (Pekrun & Perry, 2014).…”
Section: Self-efficacy Task Value and Boredommentioning
confidence: 99%
“…On the other hand, a negative task value effect and academic self-efficacy on boredom in class was found. This would mean that when students perceive the class as interesting, valuable or useful for future achievements, they experience less boredom (Goetz et al, 2010(Goetz et al, , 2006González et al, 2013;Nett et al, 2010;Pekrun et al, 2010;Sánchez Rosas & Bedis, 2015;Tze, 2011). In addition, the students' confidence in their own abilities to perform well in class would reduce boredom (Artino et al, 2010;Pekrun et al, 2011;Sánchez Rosas, 2015;Tze et al, 2013Tze et al, , 2014.…”
Section: Model Of Attention In Class: Direct Indirect and Total Effmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of emotional abilities or competences in the academic context is relevant given its impact on the general development of the students ( Costa et al, 2013 ; González et al, 2013 ; Nathanson et al, 2016 ). Several studies have suggested that academic performance is better if the students have emotional skills and are more actively involved in their own education ( Schutte et al, 2001 ; Barchard, 2003 ; Durlak et al, 2011 ; Gutiérrez-Cobo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, boredom in school has been associated with high-risk behaviors, such as drinking, drug use, car racing, and criminal actions [75,76]. It is thus important to prevent students’ from having a low commitment in the classroom, as it increases the probability of early school leaving [77].…”
Section: Discussionmentioning
confidence: 99%